2002
DOI: 10.1590/s0074-02762002000100018
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hepatitis B Virus Antigens in Paraffin-embedded Liver Specimens from the Amazon Region, Brazil

Abstract: According to the World Health Organization, hepatitis B virus (HBV) carriers account for 5% of the world population. These potential infection transmitter individuals can evolve from the asymptomatic condition to a severe hepatic damage and even hepatocellular carcinoma. A similar HBV epidemiological distribution is observed for hepatitis D virus (HDV) that shares the obligatory association to HBV for its replication (Smedile et al. 1981). Frequently related to HBV chronic carriers and less frequently to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…In chronic HBV infection, numerous studies have confirmed the heterogenous pattern of infected hepatocytes in chronic HBV infection ( Figure 1 ) where infection is spread intermittently throughout the liver in patches comprised entirely of infected cells [ 21 , 23 , 24 , 25 , 26 , 27 , 28 ] or in sparsely infected regions [ 21 , 24 , 25 , 27 , 29 , 30 ]. In many instances, HBsAg expression is detected in cells devoid of HBV DNA or HBcAg [ 26 , 28 , 31 , 32 , 33 ] ( Figure 1 ), which signals the presence of cells containing integrated HBV DNA, producing HBsAg efficiently (as SVP) but not HBV pgRNA (and HBV DNA) or other viral antigens [ 11 ].…”
Section: Distribution Of Hbv Infection In the Livermentioning
confidence: 91%
“…In chronic HBV infection, numerous studies have confirmed the heterogenous pattern of infected hepatocytes in chronic HBV infection ( Figure 1 ) where infection is spread intermittently throughout the liver in patches comprised entirely of infected cells [ 21 , 23 , 24 , 25 , 26 , 27 , 28 ] or in sparsely infected regions [ 21 , 24 , 25 , 27 , 29 , 30 ]. In many instances, HBsAg expression is detected in cells devoid of HBV DNA or HBcAg [ 26 , 28 , 31 , 32 , 33 ] ( Figure 1 ), which signals the presence of cells containing integrated HBV DNA, producing HBsAg efficiently (as SVP) but not HBV pgRNA (and HBV DNA) or other viral antigens [ 11 ].…”
Section: Distribution Of Hbv Infection In the Livermentioning
confidence: 91%
“…Observamos, em nossa casuística, a presença associada do antígeno de superfície do VHB em três casos com achados morfológicos de FA.Adicionalmente, em dois casos com características morfológicas de HL e expressão de AgHBs e/ou AgHD, houve a expressão do antígeno da FA em hepatócitos, dado ainda não referido nos trabalhos por nós estudados.Ricaurte et al (1983) referem, em trabalho de avaliação da utilização do método imuno-histoquímico para a detecção do antígeno da FA em tecido hepático, a negatividade para este antígeno em quatro casos-controle de pacientes com co-infecção por VHB e VHD. No mesmo sentido,Simonetti et al (2002), ao estudarem amostras de viscerotomias hepáticas com expressão imuno-histoquímica do AgHBs provenientes da Amazônia, a maior parte deles da região de Lábrea, pertencentes à coleção de febre amarela da Fundação Instituto Oswaldo Cruz, Rio de Janeiro, não detectam a expressão de antígeno da FA nos casos estudados por método de imuno-fluorescência, cuja sensibilidade para a detecção deste antígeno, segundo eles, é mais baixa que a da imuno-histoquímica.O encontro de expressão imuno-histoquímica de antígenos dos vírus da FA e das hepatites B e/ou Delta em um mesmo paciente nos parece interessante e viável, face à alta endemicidade destas doenças encontrada na Amazônia( Quaresma, 2003;Bensabath et al, 1987a Bensabath et al, e 1987b, principalmente se considerarmos que nossos casos são provenientes de materiais coletados em localidades próximas à floresta amazônica, onde os vetores da FA mantêm o ciclo silvestre desta doença e, o período do qual provêm estes casos, entre os anos de 1936 e 1972 precedeu, em parte, a implantação dos programas nacionais de vacinação.6.4 FibroseAté onde pudemos levantar, a avaliação de fibrose com a tipificação de fibras colágenas, presença de depósitos portais de fibras elásticas e evidências de ativação de células estreladas ainda não foram previamente estudadas nas hepatites fulminantes da Amazônia. Embora, nos casos de FA, não tenhamos detectado significativa fibrose portal, cerca de metade dos nossos casos de HL a apresentaram, predominantemente sob a forma de fibras colágenas do tipo I e de fibras elásticas.…”
unclassified